Walk the Talk: Implementing ISO 14001:2015 at a Portuguese University - Roseta-Palma, C.; Rato, V.; Farelo, C.; Simaens, A. (2nd World Symposium on Sustainability Science and Research, 2019)
Institutional sustainability, in its environmental, social and economic dimensions, is a growing concern across sectors, including Higher Education Institutions (HEI). The role of HEI in the promotion of sustainability is indisputable and the Sustainable Development Goals (SDGs) have reinforced the opportunities for HEI to provide valuable contributions in this matter, not only in their management practices, but also through their core activities in teaching, research and university extension. HEI often play a role of advocates, aiming to be agents of change through teaching and research (talk). This paper explores the practice of HEI themselves (walk), considering the growing demand for accountability of institutions of all natures. It highlights the SDGs as a pathway to link discourse and action. The paper presents a case study of the implementation of an Environmental Management System according to ISO14001:2015 at ISCTE-IUL, a Portuguese university. The implementation process proceeded in partnership with the Columbus Association, the University of Gothenburg and the University of Aveiro. Based on document analysis and the experience of the authors as participants in the process, the paper presents and discusses how the experience unfolded, emphasizing the potential of SDGs as focal points and the importance of partnerships for sustainability.